Globular chitosan prolongs the effective duration time and decreases the acute toxicity of botulinum neurotoxin after intramuscular injection in rats. (1st March 2018) - Sergeevichev, David S.; Krasilnikova, Anna A.; Strelnikov, Artem G.; Fomenko, Vladislav V.; Salakhutdinov, Nariman F.; Romanov, Alexander B.; Karaskov, Alexander M.; Pokushalov, Evgeny A.; Steinberg, Jonathan S.
Abstract: Botulinum neurotoxin (BoNT) is used for an increasing number of neurological and non-neurological indications and disorders. Since the duration of action of this neurotoxin is limited, the goal of the work was to improve the pharmacological time course of BoNT. We explored the effect of several polysaccharides on the duration of action of BoNT/A1 in rat electromyography. The formulation of BoNT/A1 containing globular chitosan increased the threshold stimulation intensity almost 2 times in 30 days after injection if compared with the baseline threshold. However, conventional linear chitosan, heparin and hyaluronic acid did not have such an effect. In addition, we compared the effectiveness of different doses of BoNT/A1 (25, 50, 75, and 100 U) with globular chitosan and compared the acute toxicity of this formulation with that of BoNT/A1 in physiological saline after intramuscular injection. The results demonstrated that the dose 25 U of BoNT/A1 with globular chitosan was both effective and safe for animals after intramuscular injection. The assessed median lethal dose (LD50 ) for intramuscular injection in rats was 1.4 times higher for a combination of BoNT/A1 with globular chitosan than that for a solution of BoNT/A1 in physiological saline. Thus, the results of our study have provided evidence that intramuscular injection of the formulation of BoNT/A1 (25 U) containing globular chitosan in rats is safe and significantly prolongs the effective duration time of BoNT/A1. Highlights: Novel methods to prolong the effective duration time of BoNT are highly needed. Globular chitosan prolongs the block of neuromuscular transmission of BoNT/A1. Globular chitosan reduces the acute toxicity of BoNT/A1. The investigated combination may represent the next generation of drug formulation.